(untitled) (Research, Society and Development, 2023)
Permanent Health Education has become increasingly essential, especially when it comes to disease prevention and health promotion. Since this factor leaves the context of scientific knowledge and encompasses several foundations between the reality and experience of each individual present, requesting the finding of a solution to the highlighted problem. Thus, the more knowledge about the reality of a given environment, the greater the probability of performing qualified and effective care, especially in Primary Care. The objective of this study is: to approach EPS as a nursing tool to improve health care in Primary Care. Methodology: This is an integrative literature review with a qualitative approach, carried out through a survey of eight studies published between 2016 and 2021, on the following platforms: VHL (Virtual Health Library) and SCIELO: (Bibliographic Database), ), using the following Health Sciences Descriptors (DeCS ): Primary Care, Permanent Education and Quality of Care, in Portuguese and English. . Data analysis was performed using the PICO strategy (P – population; I – intervention/area of ​​interest; C – comparison; O – outcomes/outcome). Results: The eight studies are published in Portuguese. The analyzed articles evidence the use of Continuing Education as a nursing tool in Primary Care, pointing out benefits such as improved care, stimuli for reflection and the ability to set goals. Conclusion: The use of Permanent Health Education by nurses in Primary Care is considered relevant, especially when applied correctly.